OP90 The impact of vision on early developing literacy. (13th September 2016) - Bruce, A; Fairley, L; Chambers, B; Wright, J; Sheldon, TA
Abstract : Background: The United Kingdom National Screening Committee recommends that vision screening should be provided to all children at age 4–5 years, the evidence supporting this recommendation is weak and the effect of reduced vision on educational attainment in children has not yet been established. At a time of change and uncertainty in the commissioning of vision screening services it is important to understand both the level of vision in the population and the impact this is likely to have on future health and social outcomes. The aim of this study is to determine the prevalence of poor vision in a multi-ethnic population and explore the impact of reduced vision on developing literacy skills in young children as they commence primary school. Methods: The study was nested within Born in Bradford (BiB) a multi-ethnic birth cohort of children (50% of South Asian origin). Measures from the universal school vision screening programme were prospectively recorded and linked to the epidemiological data and literacy measures collected from the BiB children over two consecutive school years (2012–2014). A standardised literacy measure; the Woodcock Reading Mastery Tests-Revised: Letter Identification (Letter ID) was used to measure the child's ability to identify single letters, an essential precursor to reading. The effect of presenting visual acuity (PVA) (best acuity right or left eye, with glasses if worn) on literacy (letter ID) was assessed using multi-level regression models with individuals nested within schools and adjusting for demographic and socioeconomic factors. Results: Prevalence of poor vision (worse than 0.3 logMAR) was high compared to other published studies. Unadjusted analysis (n = 2025) showed letter ID score was associated with the level of vision, with the score reducing by 2.42 points for every 1 line (0.10 logMAR) reduction in vision (95% CI: −2.98 to −1.87). When adjusted to account for demographic and socioeconomic factors the impact of vision remains significant after all factors are accounted for with letter ID score reducing by 1.65 (95% CI: −2.17 to −1.13) for every 1 line reduction in vision. Discussion: Data linkage has enabled this study to reliably demonstrate that poor vision in young children is associated with reduced early developing literacy; even after other relevant factors are taken into account. This study strengthens the argument for a national vision screening programme. Further research is required to determine the extent to which children with poor vision access treatment and the impact of such treatment not only on levels of vision but also on their educational attainment.